Employee Performance: Organizational Judgment, Career Development, and Employee Engagement: Eksplorasi Pengaruh Penilaian Organisasi dan Pengembangan Karir terhadap Kinerja Karyawan: Peran Keterlibatan Karyawan - Ana Komariya; Dewi Andriani (Academia Open, 2023)
This quantitative research study investigates the relationship between organizational judgment, career development, employee engagement, and employee performance at PT. Wood Veneer Adi Perkasa in Mojokerto City. The study aims to assess the direct and indirect effects of organizational judgment and career development on employee performance through the mediating role of employee engagement. The sample consists of 105 employees, and data collection is conducted through a questionnaire using a Likert scale. Path analysis and statistical software version 24 are employed for data analysis. The findings reveal that both organizational judgment and career development positively and significantly impact employee engagement. Additionally, organizational judgment, career development, and employee engagement have positive and significant associations with employee performance. The study highlights the importance of fostering organizational justice, providing opportunities for career development, and enhancing employee engagement to improve overall employee performance. These findings contribute to the existing body of knowledge on employee motivation and organizational behavior, offering implications for practitioners and researchers in the field. Highlights: This study explores the impact of organizational judgment and career development on employee performance through the mediating role of employee engagement. The research utilizes quantitative methods to examine the relationships between these variables. The findings indicate that organizational judgment and career development positively influence employee engagement, which in turn positively affects employee performance. Keywords: Organizational judgment, Career development, Employee engagement, Employee performance, Quantitative research